Tranexamic Acid Use in Open Reduction and Internal Fixation of Fractures of the Pelvis, Acetabulum, and Proximal Femur: A Randomized Controlled Trial. Issue 8 (August 2019) - Spitler, Clay A.; Row, Elliot R.; Gardner, Warren E.; Swafford, Rachel E.; Hankins, Michael J.; Nowotarski, Peter J.; Kiner, Dirk W.
Abstract : Objective: To assess the safety and efficacy of tranexamic acid (TXA) use in fractures of the pelvic ring, acetabulum, and proximal femur. Design: Prospective, randomized controlled trial. Setting: Single Level 1 trauma center. Patients: Forty-seven patients were randomized to the study group, and 46 patients comprised the control group. Intervention: The study group received 15 mg/kg IV TXA before incision and a second identical dose 3 hours after the initial dose. Main Outcome Measurements: Transfusion rates and total blood loss (TBL) [via hemoglobin-dilution method and rates of venous thromboembolic events (VTEs)]. Results: TBL was significantly higher in the control group (TXA = 952 mL, no TXA = 1325 mL, P = 0.028). The total transfusion rates between the TXA and control groups were not significantly different (TXA 1.51, no TXA = 1.17, P = 0.41). There were no significant differences between the TXA and control groups in inpatient VTE events ( P = 0.57). Conclusion: The use of TXA in high-energy fractures of the pelvis, acetabulum, and femur significantly decreased calculated TBL but did not decrease overall transfusion rates. TXA did not increase the rate of VTE. Further study is warranted before making broad recommendations for the use of TXA in these fractures. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.